The Infanticide in Marie-Célie Agnant’s Le Livre d’Emma or Colonized Caring Made Manifest - Boum Make, Jennifer (MuseMedusa)

(untitled) (Département des littératures de langue française (Université de Montréal), 2022)
Le livre d’Emma (2001) by Marie-Célie Agnant recounts the story of Emma Bratte following the murder of her young daughter, Lola. Flore, who is also the narrator of the story, meets Emma at the psychiatric ward where she is confined: she is tasked with acting as an interpreter since Emma refuses to speak any language but Haitian Creole. It is during the sessions with Flore that Emma speaks of “la malédiction du sang”, a blood-borne curse originating with the slave trade and colonization. This generational curse refers to the oppression and exploitation that enslaved people were subjected to, related in particular to women’s reproductive labor, and the perpetuation of exploitative care into the present. As such, rather than read the infanticide as the result of Emma’s alleged madness, I read the commonly perceived violent act of infanticide as the signifier for the persistent defects of configurations of care giving and care receiving in colonial and postcolonial societies.